2017
DOI: 10.1038/s41598-017-11408-5
|View full text |Cite
|
Sign up to set email alerts
|

Carnosic acid prevents dextran sulfate sodium-induced acute colitis associated with the regulation of the Keap1/Nrf2 pathway

Abstract: Crohn’s disease and ulcerative colitis are inflammatory bowel diseases (IBDs) with high prevalence in humans. Carnosic acid (CA) has been reported to possess antioxidative properties; however, its role in IBDs has not been determined. In the present study, we found that CA significantly prevented the loss of body weight and shortening of colon length in acute colitis induced by dextran sodium sulfate (DSS). Pronounced infiltration of immune cells and a loss of crypt architecture and goblet cells were ameliorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 43 publications
(41 reference statements)
4
35
0
Order By: Relevance
“…The antioxidants SOD and NQO-1 directly eliminate free superoxide radicals to protect against lipid peroxidation [50,51]. Previous reports of acute gut inflammation in the DSS model observed a significant increase in lipid peroxidation and reduced levels of antioxidant enzymes (NQO-1 and SOD) [18,19,[52][53][54][55][56], which were replicated in the present study. We also observed a significant reduction in MDA levels after treatment with idebenone, which is consistent with a previous report where idebenone effectively suppressed lipid peroxidation in brain mitochondria [57].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The antioxidants SOD and NQO-1 directly eliminate free superoxide radicals to protect against lipid peroxidation [50,51]. Previous reports of acute gut inflammation in the DSS model observed a significant increase in lipid peroxidation and reduced levels of antioxidant enzymes (NQO-1 and SOD) [18,19,[52][53][54][55][56], which were replicated in the present study. We also observed a significant reduction in MDA levels after treatment with idebenone, which is consistent with a previous report where idebenone effectively suppressed lipid peroxidation in brain mitochondria [57].…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, at present, it is not possible to align the multiple contradicting results of the reported clinical trials. On the other side, a plethora of literature supports the role of oxidative stress in UC and consequently justifies the use of antioxidants as a therapeutic strategy [15,27,52,54,60,[98][99][100][101][102]. Since UC is a multifactorial disease, pharmacological targeting of individual factors appears of limited use to provide effective and sustainable therapy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been substantially demonstrated that nuclear factor (erythroid derived 2)-like 2 (Nrf2), a redox-sensitive transcription factor, as well as its tight interact with Kelch-like ECH-associated protein 1 (Keap1) could promote the antioxidant activity and provide therapeutic benefits in inflammation and associated disorders. Keap1/Nrf-2 signaling pathway plays a key role in the protection of intestinal cells against oxidative stress ( Yang N. et al, 2017 ). Therefore, the mRNA expressions of Keap1 ( Figure 6A ) and Nrf-2 ( Figure 6B ) were measured by real-time quantitative PCR.…”
Section: Resultsmentioning
confidence: 99%
“…The nuclear receptor PXR and the transcription factor Nrf2 play important roles in elevating MDR1 gene transcription and ultimately increasing P-gp function (Chen et al, 2012;Jeddi et al, 2018). Additionally, dysregulation of PXR/Nrf2 activity in the intestine is thought to contribute to colitis pathophysiology (Khor et al, 2006;Yang et al, 2017). In the present study of DSS-induced colitis rats, PXR and Nrf2 expression were decreased in the colon, in accordance with previous studies (Hu et al, 2014;Yang et al, 2017); however, in the berberine-treated group, only the decrease in Nrf2 expression was reversed by berberine, with no effect observed on PXR expression ( Fig.…”
Section: Discussionmentioning
confidence: 99%